The prevalence of SARS-CoV-2 antibodies in triage-negative patients and staff of a fertility setting from lockdown release throughout 2020. Issue 3 (27th July 2021) - Manolea, Corina; Capitanescu, Andrei; Borș, Roxana; Rugescu, Ioana; Bechir, Melihan; Mehedintu, Claudia; Varlas, Valentin
Abstract: STUDY QUESTION: What is the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies in triage-negative patients undergoing ART and fertility care providers after lockdown release and throughout 2020? SUMMARY ANSWER: Out of the triage-negative patients whose blood samples were assessed for SARS-CoV-2 antibodies over 6 months, 5.2% yielded positive results with a significantly higher rate in health care workers (HCWs) and a significant month-by-month increase in those with evidence of antibodies. WHAT IS KNOWN ALREADY: Patients of reproductive age are more prone to asymptomatic or minimal forms of coronavirus disease 2019 (COVID-19) as compared to older age groups, and the identification of those with active infection and those already exposed (and probably immunized) is important for safety and cost-effective use of testing resources in the fertility setting. Data on the prevalence of SARS-CoV-2 in ART patients are limited and encompass short time frames; current rates are unknown. There is also no consensus on the optimal way of screening triage-negative ART patients in moderate/high-risk areas. STUDY DESIGN, SIZE, DURATION: A prospective longitudinal unicentric study on triage negative ART patients (n = 516) and clinical staff (n = 30) was carried out. We analyzed 705 serological tests for SARS-CoV-2 sampled between 17 May 2020 (the first working day after lockdown release) up to 1 December 2020, to assess the positivity rates for SARS-CoV-2 antibodies. PARTICIPANTS/MATERIALS, SETTING, METHODS: We collected data on the serological status for IgM and IgG antibodies against SARS-CoV-2 in 516 triage-negative men (n = 123) and women (n = 393) undergoing ART at a private fertility center and 30 HCWs that were at work during the study period. Antibodies were detected with a capture chemiluminescence assay (CLIA) targeting the highly Immunogenic S1 and S2 domains on the virus spike protein. We also analyzed the molecular test results of the cases exhibiting a positive serology. MAIN RESULTS AND THE ROLE OF CHANCE: The data showed that 5.2% of the triage-negative ART patients had a positive serological result for SARS-CoV-2, with an overall conversion rate of 2.1% for IgG and 4.6% for IgM. There was no significant difference in seroprevalence between sexes. The small cohort (n = 30) of HCWs had a markedly increased seroprevalence (12.9% for Ig M and 22.6% for IgG). The highest seropositivity in our cohort was recorded in November (16.2%). The IgM positivity rates revealed significant monthly increments, paralleling official prevalence rates based on nasopharyngeal swabs. No positive molecular tests were identified in cases exhibiting a solitary positive IgG result. We show that despite a 6-fold increase in the number of ART patients with a positive serology between May and December 2020, most of our patients remain unexposed to the virus. The study was undertaken in a high-risk area for COVID-19, with a 20-times increase in the active cases across the study period. LIMITATIONS, REASONS FOR CAUTION: The geographical restriction, alongside the lack of running a second, differently-targeted immunoassay (orthogonal testing), could limit the generalizability and translation of our results to other fertility settings or other immunoassays. WIDER IMPLICATIONS OF THE FINDINGS: The low positivity rates for IgG against the SARS-CoV-2 spike protein seen at the end of 2020 imply that most of the fertility patients are still at risk for SARS-CoV-2 infection. Until mass vaccination and other measures effectively diminish the pandemic, risk mitigation strategies must be maintained in the fertility units in the foreseeable future. Patients with a solitary IgG+ status are most likely 'non-infectious' and can elude further testing without giving up the strict use of universal protective measures. With increasing seroprevalences owing to infection or vaccination, and with the consecutive increase in test performance, it is possible that serological screening of ART patients might be more cost-effective than PCR testing, especially for the many patients with repeat treatments/procedures in a time-frame of months. STUDY FUNDING/COMPETING INTERESTS: This research received no external funding. All authors declare having no conflict of interest with regard to this trial.